Shamba Shape Up: Series 2 and 3 Knowledge Attitude and Practice (KAP) Report - Mediae (Mediae Company, 2013)
This report summarizes the findings of the research for the second and third series in terms of the audience knowledge, attitudes and practices (KAP) in Kenya. The field research and cross tabulation in 2013 was carried out by Research Guide Africa, an independent research organisation